Analisis Keterampilan Berpikir Kreatif Peserta Didik Melalui Model Project Based Learning Pada Materi Bencana Alam di UPT SMPN 10 Gresik - Najichah, Zuhrotun; Arum, Wahyuni Fajar; Wakhidah, Nur (Experiment: Journal of Science Education, 2024)
This study aims to analyze the creative thinking skills of students on natural disaster material using the PjBL model at UPT SMPN 10 Gresik. This study uses a quantitative descriptive method with 32 randomly selected eighth-grade students as participants. The research instrument consisted of an observation sheet that measured indicators of creative thinking based on the Torrance model, namely fluency, flexibility, originality, and elaboration. The research results show that the level of creative thinking among students varies, with 31.25% categorized as very creative, 28.10% as creative, and 40.63% as somewhat creative. The indicator with the highest achievement is fluency (72%), while the elaboration indicator has the lowest achievement (40%).